Fasting: A Sacramental - Thurutbimattam, Philip (Journal of Dharma, 1984)
Hunger or starvation is never sought as a goal, though for millions today it is a daily lived experience. Although deprivation of essential goods for one’s maintenance is also never viewed as something holy or ideal, the world religions have regarded fasting as a powerful means for attaining the spiritual benefits. Whether voluntarily undertaken or imposed by the religious authority, such fasting is a sacramental in both western and eastern religions and so this article proposes to examine various aspects of it in these religious traditions.